Penggunaan Pasco Capstone 14.1 untuk Menentukan Koefisien Konveksi Udara dengan Metode Pendinginan Air - Taat Guswantoro (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2017)
Water cooling occurs since the heat energy of water is transferred to the air. Water is placed in a thin transparant vessel can reduce the effects of heat transfer by radiation and conduction, so the most dominant heat transfer is convection. Newton's law of cooling states that the rate of cooling is directly proportional to the temperature difference between the object and room temperature. By knowing the value of constant cooling, the air convection coefficient can be calculated. This study using three different sizes of cups, each of which is filled with hot water. In each glass inserted temperature sensors that connected to the interface, recording the temperature every 60 seconds using pasco capstone 14.1. The resulting graph was analyzed by exponential regression, in order to find the value of constant cooling, from this value can be calculated the air convection coefficient. The research result shows air convection coefficient value of W/m2OC, that mean if there is an object that has an area of 1 m2 and 1OC higher than room temperature, the thermal energy of the object will be lost of 19.9 J for each second. Keywords: Water cooling, heat transfer, air convection coefficient.